Role of Chronobiology in Determining the Distribution of Non-Communicable Diseases across Geographies-Thinking beyond Diet - Raina SK; Maria A; Gandhi MK (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2022)
Background: Over the last few years, it is being realised that the increasing burden of non-communicable diseases ( NCDs) may be linked to some macro-level determinants. Material and Methods: The present systematic review uses data distributed across geographies to explore the role played by chronobiology. Results: The paper is based on the role of these factors in affecting the prevalence of diabetes, hypertension and dementia. The paper uses extensive empirical scrutiny, covering areas across a state and applying the outcome of these to generate a hypothesis. Conclusion: Our results though initial indicate that change in chronotype appears to contribute to an increase in NCDs.